Pro-Kontra dan Prospektif Kewenangan Uji Konstitusionalitas Perpu - Iskandar Muda (Jurnal Konstitusi, 2016)
Pros and cons of the authority to deal with judicial constitutionality review of Government Regulation in Lieu of Law (Perpu) either from fellow judges of the Constitutional Court (MK) or from the world of legal science is acceptable. The pros and cons is not due to the differences in interests between them, but it is caused by the differences in schools or schools of thought and interpretation methodologies adopted. The authority of the Constitutional Court to review the constitutionality of Perpu is in line with the philosophy of Judicial Activism (the concept of active understanding) which is identical to the "Statue of the Goddess of Justice" whose eyes are not closed in order to be able to watch and absorb the "sense of social justice", to incorporate the living legal values in the society, respond to the demand and aspiration of the people and, furthermore, to create “the thinking judges” which make their decisions responsive. However, the authority of the Court to review the constitutionality of the Perpu might cause “broader impacts” in the future which means that the impact will not be only on the constitutionality review of the Perpu but also on the other decisions of Constitutional Court.